2021
DOI: 10.1590/1807-3107bor-2021.vol35.0099
|View full text |Cite
|
Sign up to set email alerts
|

LASER in periodontal treatment: is it an effective treatment or science fiction?

Abstract: There are several studies that evaluate the use of lasers in periodontal treatment in non-surgical or surgical therapy. However, while several studies showed clinically beneficial effects of some lasers in periodontal treatment, there are few clinical reports of additional advantages of lasers as adjunctive treatments in periodontology. The aim of this paper is to demonstrate and critically analyze the level of scientific evidence of effects of low-level lasers and high-power lasers in periodontology. A narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 123 publications
0
19
0
3
Order By: Relevance
“…Severe periodontitis is one of the difficult aspects of periodontal treatment due to the fact that severe periodontitis not only destroys the periodontal tissue [ 1 ], but it also leaves the pulp in a subclinical state through periodontal pulp traffic branches, and the presence of diseased pulp will prevent the healing of periodontal tissue after periodontal treatment [ 2 ]. Severe periodontitis is a common disease in dentistry, the onset of which is associated with multiple factors, and early patients have no obvious symptoms, mostly just secondary gingival bleeding or halitosis, with symptoms similar to gingival inflammation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe periodontitis is one of the difficult aspects of periodontal treatment due to the fact that severe periodontitis not only destroys the periodontal tissue [ 1 ], but it also leaves the pulp in a subclinical state through periodontal pulp traffic branches, and the presence of diseased pulp will prevent the healing of periodontal tissue after periodontal treatment [ 2 ]. Severe periodontitis is a common disease in dentistry, the onset of which is associated with multiple factors, and early patients have no obvious symptoms, mostly just secondary gingival bleeding or halitosis, with symptoms similar to gingival inflammation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like other types of electromagnetic radiation, laser causes warming at lower doses and injury at higher absorbed energies. Although low-energy lasers are used for the periodontal treatment, several systematic reviews have found no proven clinical benefits, while some studies have shown controversial results and questioned effectiveness [71]. Theoretically, a non-thermal photochemical antimicrobial effect of laser is possible; but studies with temperature measurements are needed to prevent thermal damage of atrophic tissues.…”
Section: Gingival Recession and Periodontal Diseasementioning
confidence: 99%
“…Other laser applications (photoablative, photodynamic therapy, removal of diseased pocket lining epithelium, etc.) are beyond the scope of this review [71][72][73]. Furthermore, the calculus removal (scaling and root planing) is often provided.…”
Section: Gingival Recession and Periodontal Diseasementioning
confidence: 99%
“…Laser treatment is promoted for patients who have difficulty with bleeding on surgical treatment or with use of anesthesia. Laser treatment of periodontal disease is classified into high power laser treatment (HPLT) and low-level laser treatment (LLLT), depending on the power of the laser used [ 160 ]. HPLT is mainly used for the removal of calculus and inflammatory substances on the root surface, the removal of granulation tissue during periodontal surgery, hemostasis, and gingivectomy.…”
Section: Next-generation Procedures In Periodontal Diseasementioning
confidence: 99%